Preliminary study of microplastics content in the digestive tract of sea cucumber from Demak Waters. Issue 1 (1st January 2023) - Hartati, R; Widianingsih, W; Zainuri, M; Supriyo, E
Abstract: As a marine delicacy, sea cucumbers were often eaten raw in many part of the world and they have been reported to ingest microplastic. This study aimed to determine the microplastics in the digestive system of sea cucumbers from Demak Waters. The ten samples of Acaudina sp were taken using a bottom dredge from Wulan Estury and put in the glass-bottles samples. In the laboratory, the digestive tract was taken out from the sea cucumber, divided into 7 parts, and pooled in the glass beaker. Microplastics were digested with KOH and incubated at 40 °C for 24 hours. Then, the digestion solution was filtered through a sterile cellulose nitrate filter paper by vacuum filtration. The microplastics obtained were observed for their physical characteristics (density, shape and colour) under the microscope. The density of microplastics were varied among the part of digestive tract. They consisted of fragments, fiber, and pellets. The colour of microplastics were varied but dominated by the blue. As a deposit feeder, the sea cucumber might ingest the microplastics in the sediment they fed on.